2017
DOI: 10.1111/andr.12358
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use and serum testosterone concentrations among U.S. males

Abstract: Background Marijuana has been reported to have several effects on the male reproductive system. Marijuana has previously been linked to reduced adult testosterone, however, a study in Denmark reported increased testosterone concentrations among marijuana users. This study was performed to estimate the effect of marijuana use on testosterone in U.S. males. Methods Data on serum testosterone, marijuana use and covariates for 1577 men from the 2011–2012 U.S. National Health and Nutrition Examination Survey (NHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 31 publications
1
43
4
Order By: Relevance
“…However, when controlling for other variables, neither cannabis-use nor the percentage of cannabis-positive urine drug screens within the 15-month study period were significantly associated with serum testosterone. These results suggest that cannabis use is not associated with serum testosterone levels in this population of men, despite findings from previous studies to suggest that frequency and/or recency of cannabis use may be associated with higher serum testosterone levels [4][5][6]. However, due to the limited literature in the field, it is unclear whether our results are generalizable outside of the male MMT population.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…However, when controlling for other variables, neither cannabis-use nor the percentage of cannabis-positive urine drug screens within the 15-month study period were significantly associated with serum testosterone. These results suggest that cannabis use is not associated with serum testosterone levels in this population of men, despite findings from previous studies to suggest that frequency and/or recency of cannabis use may be associated with higher serum testosterone levels [4][5][6]. However, due to the limited literature in the field, it is unclear whether our results are generalizable outside of the male MMT population.…”
Section: Discussioncontrasting
confidence: 88%
“…The variability in study design, sampling methods, and lack of consistent results render these studies inconclusive [7]. However, there are three larger and more recent questionnaire-based studies that reported correlations between cannabis use and serum testosterone levels [4][5][6]. In a study of 1215 Danish men aged 18-28, Gundersen et al found that testosterone was 7% (95% CI: 0, 14) higher in those that used cannabis more than once weekly, compared to never users [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent population study on over 1,500 U.S. men found no differences in serum testosterone levels among ever users of marijuana compared to never users. However, testosterone concentrations were higher in men with more recent marijuana use, especially in men aged 18-29 [78]. A study on over 1,200 young healthy men reported, similarly to tobacco smokers, an increase in testosterone levels in marijuana smokers [79].…”
Section: Effects On Testosterone Productionmentioning
confidence: 99%